The Effect of Using Image Media to Increase English Learning Outcomes for Class 6 Students at Elementary School: Pengaruh Penggunaan Media Gambar Untuk Meningkatkan Hasil Belajar Bahasa Inggris Siswa Kelas 6 SD - Salmee Mahama; Moch. Bahak Udin Arifin (Universitas Muhammadiyah Sidoarjo, 2021)
The problem raised in this study is whether there is an effect of applying the use of image media to improve English learning outcomes for 6th grade students at yahoo Elementary school Thailand.The purpose of this study was to find out the achievements in developing descriptive text writing for 6th graders of Yaho elementary school before and after being taught using picture media. This research was conducted in the 6th grade of Yahoo elementary school. The sampel of this study were 19 students in the class. This research method is quantitative with a pre-experimental design. To get the data, the researcher gave pre-test, treatment and post-test to the students. Researchers use image media to teach writing descriptive text. Based on the results of the study, the researchers found that there were significant differences in students' achievement in writing descriptive texts. In conclusion, using image media in teaching writing affective descriptive text to improve students' writing achievement in writing descriptive text.